Predictive value of atherogenic index of plasma in combination with diagonal earlobe crease in coronary heart disease - Guo, Ruoling; Sun, Mingliang; Yang, Huihui; Dou, Jie; Gao, Jie; Liu, Tong; Cheng, Fei; Luo, Donglei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe atherogenic index of plasma (AIP) and diagonal earlobe crease (DELC) are correlated with the incidence of coronary heart disease (CHD). Nevertheless, the role of AIP and DELC in the characterization and prediction of CHD remains underexplored.MethodsThis study enrolled a total of 1,378 patients suspected to be indicative of CHD, all of whom were admitted to Chengde Central Hospital between September 2021 and August 2024. Based on coronary angiography (CAG), the cohort was stratified into two groups: the CHD group (n = 1,071) and the non-CHD group (n = 307). Multivariate logistic analysis was used to analyze the interplay of AIP, DELC, and CHD. The predictive value of AIP and DELC for CHD was evaluated by nomogram, calibration curves, and receiver operating characteristic (ROC).ResultsThe results showed that AIP and DELC were positively correlated with CHD. Age, gender, hypertension, diabetes mellitus (DM), aspartate aminotransferase (AST), AIP, creatinine (CR), and DELC were independent risk factors for CHD. AIP was correlated with the Gensini score, indicating that as AIP levels rise, the severity of CHD intensifies. A progressive increase in DELC positivity was observed with higher Gensini scores. The diagnostic model for CHD was constructed based on the above risk factors. The area under the curve (AUC) for the integrated application of AIP and DELC was 0.702, highlighting the model's considerable diagnostic efficacy in the identification of CHD.ConclusionsAIP and DELC were independent risk factors for CHD. The combination of the two factors exhibited great predictive value for the diagnosis of CHD.